Improving Student Mathematics Learning Outcomes in Algebraic Factorization Material Using the Method Team Accelerated Instruction - Dwi Julianti; Achmad Ruslan Afendi (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Improving student learning outcomes in algebraic factorization material is the aim of this research, through classroom action research using cooperative learning methods.Team Accelerated Instruction. This research was carried out at SMP Muhammadiyah 5 Samarinda with the research subjects being thirty-eight class VIII students. The instruments used are assignments, end-of-cycle tests and observations. Data analysis techniques use descriptive statistics in the form of averages and percentages. The person acting as the learning implementer is the researcher, while the observer is the class VIII mathematics teacher at SMP Muhammadiyah 5 and a female student. The results of data analysis show an increase in the average final score for each cycle. The basic value for cycle I was obtained from the initial ability test results of 43.88 before cooperative learning typeTeam Accelerated Instruction started. In cycle I the basic value increased from the basic average value of 43.88 to 50.05. In cycle II, the average value of learning outcomes increased to 58.88 and in cycle III the average value of learning outcomes increased to 73. So the cycle was stopped because the average value of students' mathematics learning outcomes had reached the minimum completeness criteria of 70. Conclusion This research shows that there is an increase in students' mathematics learning outcomes through cooperative learning Team Accelerated Instruction on algebraic term factorization material in class VIII SMP Muhammadiyah 5 Samarinda.